PERAN ORANGTUA DAN PEMBINA REMAJA KRISTEN TERHADAP FENOMENA PERILAKU REMAJA CITAYAM - Linda Widjaja; Yanto Paulus Hermanto; Josep Tatang (Phronesis: Jurnal Teologi dan Misi, 2022)
The role of parents and youth coaches in the growth and development of adolescent life is significant. This is because there is much news about teenage problems, such as teenage fights, school shootings, alcohol-related accidents, drugs, early pregnancy outside marriage, and teen suicide. Juvenile delinquency due to dropping out of school and lack of parental attention is also often a problem. Adolescent problems can extend to whole communities, schools, churches, cities, and countries. Teenagers at their critical age are trying to find their identity after going through childhood to adult humans. All positive and negative influences in teenagers' lives tend to be easily absorbed, studied, and carried out, even though many are developed as innovations from their creativity. The presence of the adolescent phenomenon from Citayam has recently become the author's interest to examine the role of parents and youth coaches in responding to their influence on teenagers as the next generation of the Kingdom of God. The phenomenon of Citayam youth brings positive and negative impacts and brings a new challenge for parents and youth coaches to answer the challenges of today's youth. This research was made using a qualitative literature study from the Bible, books about teenagers, articles, and social media content about the Citayam youth phenomenon.